THE GENERALIZED ENTROPIC PROPERTY FOR THE MONO-$n$-ARY ALGEBRA - Ehsani, Amir (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
In this paper we show by using the laws of pseudo-distributivity that every idempotent and commutative algebra with one n-ary operation satisfying the generalized entropic property is entropic.
Keywords: complex algebra; mode; entropic algebra; generalized entropic property